Remote Steric Control for Site-Selective Synthesis - Asako, Sobi; Ilies, Laurean (Synlett, 2023)
Control of site selectivity for organic synthesis in general, and for transition-metal-catalyzed C–H functionalization in particular, is an important and challenging task. Steric interactions have been widely used to control reaction selectivity, but these strategies are largely limited to proximity sites. Recently, control of site selectivity through remote steric interactions has emerged as an attractive strategy that can enable selective reactions at distal sites from a steric marker. This review will cover recent developments in this area, with a focus on borylation reactions and transition-metal-catalyzed C–H activation.
Keywords: steric control; site selectivity; remote control; C–H activation; transition-metal catalysis